2014
DOI: 10.3892/or.2014.3127
|View full text |Cite
|
Sign up to set email alerts
|

CDK2 and CDK4 play important roles in promoting the proliferation of SKOV3 ovarian carcinoma cells induced by tumor-associated macrophages

Abstract: A large quantity of M2-polarized tumor-associated macrophages (TAMs) is present in the tissue, ascitic fluid and peritoneum of ovarian cancer patients. A thorough understanding of the roles of M2-TAM in the development of ovarian cancer may provide new insight into the treatment of this disease. The rapid advancement of omics techniques presents a great challenge to biologists to extract meaningful biological information from vast pools of data. In the present study, using microarray method, we identified 996 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Cyclin D1 levels are also posttranslationally regulated by its degradation through the following ubiquitin-proteasome pathway. In addition, CDK2 binds to cyclin E or cyclin A, and exclusively promotes the G1/S phase transition in mitosis [22][23][24]. In this study, we showed that SDF-1 increased the active level of Cyclin D1 and CDK2.…”
Section: Discussionmentioning
confidence: 68%
“…Cyclin D1 levels are also posttranslationally regulated by its degradation through the following ubiquitin-proteasome pathway. In addition, CDK2 binds to cyclin E or cyclin A, and exclusively promotes the G1/S phase transition in mitosis [22][23][24]. In this study, we showed that SDF-1 increased the active level of Cyclin D1 and CDK2.…”
Section: Discussionmentioning
confidence: 68%
“…Cyclin D1 levels are also post-translationally regulated by its degradation through the following ubiquitinproteasome pathway. In addition, CDK2 binds to cyclin E or cyclin A and exclusively promotes the G1/S phase transition and that Cdc2/cyclin B complexes play a major role in mitosis [24][25][26]. In this study, we showed that TGF-β1 increased the active level of CDK2 and Cyclin D1.…”
Section: Discussionmentioning
confidence: 70%
“…In ovarian tumors, it is also shown that some cyclindependent kinases (CDK2, CDK4, CDK6, CDK12) were closely related to the survival and therapy for ovarian cancer patients [13][14][15][16]. Moreover, in several human cancers, the role of CDK1 has been well characterized.…”
Section: Discussionmentioning
confidence: 97%